2023
DOI: 10.1021/jacs.3c03757
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Polymer Hybrids via Direct and Site-Selective Acylation with the ATRP Initiator and Photoinduced Polymerization

Abstract: Combining synthetic polymers with RNA paves the way for creating RNA-based materials with non-canonical functions. We have developed an acylation reagent that allows for direct incorporation of the atom transfer radical polymerization (ATRP) initiator into both short synthetic oligoribonucleotides and natural biomass RNA extracted from torula yeast. The acylation was performed in a quantitative yield. The resulting initiator-functionalized RNAs were used for grafting polymer chains from the RNA by photoinduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 69 publications
(150 reference statements)
0
10
0
Order By: Relevance
“…Aqueous photo-RDRP can be used to prepare well-defined bioconjugates for biomedical applications. ,, Since nucleic acids have negligible absorption in the red light range, we attempted to synthesize DNA-based bioconjugates using MB + /Cu-catalyzed photo-ATRP. To test the feasibility of this mild dual-catalytic system in the synthesis of biohybrids, we prepared a DNA–polymer bioconjugate by the “grafting-from” approach (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous photo-RDRP can be used to prepare well-defined bioconjugates for biomedical applications. ,, Since nucleic acids have negligible absorption in the red light range, we attempted to synthesize DNA-based bioconjugates using MB + /Cu-catalyzed photo-ATRP. To test the feasibility of this mild dual-catalytic system in the synthesis of biohybrids, we prepared a DNA–polymer bioconjugate by the “grafting-from” approach (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…To test the feasibility of this mild dual-catalytic system in the synthesis of biohybrids, we prepared a DNA–polymer bioconjugate by the “grafting-from” approach (Figure ). DNA functionalized with a single ATRP initiator at the 5′ terminal (T 10 -Br) was synthesized as previously reported , and then used for chain extension with the hydrophilic OEOMA 500 under the optimized conditions using the molar ratio [OEOMA 500 ]/[T 10 -Br]/[MB + ]/[CuBr 2 ]/[TPMA] = 400/1/0.05/0.6/1.8. After 30 min of red light irradiation, a well-defined bioconjugate (DNA- b -pOEOMA 500 ) was obtained with 76% monomer conversion, excellent correlation between M n,th and M n,MALS , and low dispersity ( Đ = 1.27).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we synthesized acrylamido RNA crosslinkers under different acylation conditions (% DMSO v/v in water and the amount of AAm-AI ), and the degree of acylation was determined using 1 H NMR, according to the previously reported procedure (Figure S5). As shown in Figure B, conducting RNA modification with a higher concentration of DMSO in water or using a larger amount of AAm-AI resulted in an increased number of acrylamide incorporation in the RNA. It should be noted that up to superstoichiometric yield (12.8 acrylamide groups per 10 ribonucleotides) could be achieved when RNA was treated with 3 equiv (3×) of AAm-AI compared with ribonucleotide in 100% DMSO overnight.…”
Section: Results and Discussionmentioning
confidence: 97%
“…Consequently, acyl imidazole chemistry has been extensively studied for the structural mapping of RNA (i.e., selective 2′-hydroxyl acylation analyzed by primer extension, SHAPE) in vitro and in vivo . We have recently demonstrated that RNA can be modified with acyl imidazole reagents to serve as an atom transfer radical polymerization (ATRP) initiator under the mild and biocompatible polymerization conditions . Additionally, it is important to note that during the radical polymerization process vinyl monomers could undergo copolymerization with two or more different types of monomers.…”
Section: Introductionmentioning
confidence: 99%
“…11–15 This advancement enables the synthesis of well-defined polymers with complex structures, like protein–polymers and nucleic acid–polymer hybrids. 16–18…”
mentioning
confidence: 99%